Friction increasing treatment process for steel rail joint fishplate
By constructing a composite friction-enhancing coating on the fishplate of the rail joint, the problem of low friction coefficient was solved, achieving efficient locking of the joint, improving the stability and safety of the track, and extending its service life.
Patent Information
- Application Number
- CN202511195384.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-25
- Publication Date
- 2025-12-02
AI Technical Summary
In existing technologies, the friction coefficient between the fishplate and the rail joint is low, resulting in insufficient longitudinal resistance of the joint. This makes it unable to effectively resist the expansion and contraction stress of the rail caused by temperature changes, and the rail gap width is prone to change with the ambient temperature, affecting the stability and electrical performance of the track.
A friction-enhancing process for fishplates of rail joints is adopted. By modifying the surface of the fishplate substrate, a composite coating structure is constructed, consisting of an epoxy silane coupling agent underlayer, a high-strength epoxy resin matrix binder layer, and hard wear-resistant aggregate. The coating is then cross-linked and cured by thermosetting to form a friction-enhancing coating with stable physicochemical properties.
It significantly improves the static friction coefficient between the fishplate and the rail, increasing it from 0.3 to over 0.65, enhancing the locking ability of the joint, stabilizing the rail gap width, improving traffic safety and track structure reliability, reducing traffic safety risks caused by joint problems, and extending service life.
Smart Images

Figure CN121042231A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of metal material surface treatment technology, specifically a friction-enhancing treatment process for fishplates of rail joints. Background Technology
[0002] As a crucial artery for passenger and freight transport in modern society, the safe, efficient, and stable operation of railway transportation systems largely depends on the integrity and reliability of the track structure. Within this structure, rail joints, as the fundamental building blocks connecting two rail sections and ensuring track continuity, directly impact the smoothness of train operation and even fundamental traffic safety through their mechanical properties and working condition. Rail joints not only need to withstand the enormous vertical impact and lateral forces from train wheelsets but also must cope with the significant longitudinal temperature stress generated within the rails due to changes in ambient temperature. Especially in sections with track circuits, rail insulated joints also play a crucial role in electrically isolating the rails on both sides to ensure the normal transmission of track circuit signals. Therefore, the design and maintenance of rail joints have always been core technical issues of concern in the field of track engineering.
[0003] The patent publication number "CN201024360Y" discloses an improved shock-absorbing fishplate, which is a clamping structure formed by combining a raised strip main plate and a regular fishplate secondary plate. The main and secondary clamping plates have a double-ribbed, grooved structure on the side opposite to the rail. The groove is provided with fastening bolt holes. In the application state, the main and secondary plates are fastened to the joint of the two rails with bolts. The upper surface of the main plate gradually rises from both sides to the middle, forming a double-slope upper surface at the joint of the two rails that is higher than the bearing surface of the connected rails.
[0004] As shown in the above technology, in existing technical practices, rail joints commonly employ a fishplate and high-strength bolt fastening scheme. Specifically, a fishplate is placed on each side of the web of two rails, and a pre-tightening torque is applied using high-strength bolts passing through pre-drilled holes in the fishplate and web to firmly clamp the fishplate onto the rail. The design principle of this technical solution is that the tightening torque of the bolts generates a huge positive pressure at the contact interface between the fishplate and the rail, mainly in the contact areas between the upper and lower jaws of the fishplate and the lower part of the rail head and the upper part of the rail base. This positive pressure, multiplied by the inherent friction coefficient of the steel itself, forms a longitudinal resistance at the joint that prevents the rail from sliding along the track. Ideally, this longitudinal resistance should be sufficient to overcome the expansion and contraction stress of the rail caused by temperature changes. Locking the rail gap width within a stable and reasonable range to maintain the geometric stability of the track and the electrical performance of the track circuit—this technical solution, which relies on mechanical clamping force to generate frictional resistance—has been widely used in railway construction and operation for a long time due to its simple structure, convenient installation, and controllable cost, forming the basis of current rail joint technology. In existing technologies, the fishplate of the rail joint does not employ friction-enhancing technology, resulting in a low coefficient of friction between the fishplate and the rail, leading to relatively low frictional resistance. Currently, increasing the frictional resistance between the fishplate and the rail can only be achieved by increasing the tightening torque of the joint bolts. However, increasing the tightening torque is limited by factors such as bolt strength and ease of on-site installation, and the tightening torque cannot be too high. Therefore, in existing technologies, the frictional resistance between the fishplate and the rail cannot overcome the temperature stress of the rail, the rail gap width of the rail joint easily changes with ambient temperature, and the joint locking ability is weak. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a friction-enhancing process for rail joint fishplates, which solves the problem of low friction coefficient between the rail and the fishplate.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a friction-enhancing treatment process for a fishplate of a rail joint, applied to surface modification of a fishplate substrate, the process comprising the following steps in a predetermined order: Step 1: Substrate pretreatment stage, used to form a clean, rough bonding interface with high surface energy on the working surface to be treated of the fishtail plate substrate. Step 2: Multi-layer composite friction-enhancing coating application stage, used to construct a composite coating structure on the pretreated working surface, consisting of an epoxy silane coupling agent underlayer, a high-strength epoxy resin matrix binder layer, and hard wear-resistant aggregate; Step 3: Thermal curing and post-treatment stage, used to fully cross-link and cure the composite coating structure to form a final friction-enhancing coating area with stable physicochemical properties, and to remove excess surface deposits.
[0007] Preferably, the substrate pretreatment stage specifically includes the following sub-steps in sequence: Surface mechanical cleaning treatment steps: Sandblasting is used to thoroughly sandblast the entire surface of the fishtail plate substrate, especially the upper and lower jaw areas that will contact the rail, to remove oxide scale, rust and other attached contaminants from the surface and form a uniform roughened surface. Chemical degreasing and cleaning process: The fish tail plate substrate that has undergone mechanical purification is immersed in an ultrasonic cleaning tank containing an alkaline degreasing agent aqueous solution to remove grease, dust and other organic pollutants remaining in the micropores on its surface. Then, it is sequentially subjected to high-pressure hot water rinsing, deionized water rinsing and compressed air drying. Surface activation and adhesion enhancement treatment steps: The clean and dry working surface of the fishtail plate substrate is exposed and immersed in the phosphating solution for treatment until a dense, uniform phosphate conversion film with a microporous structure is formed on its surface to increase the specific surface area of the substrate and provide a mechanical bonding basis for subsequent coatings.
[0008] Preferably, in the surface mechanical cleaning treatment step, angular steel grit or alumina abrasive is used as the blasting medium. The abrasive has a particle size grade of G40 and is blasted under compressed air driven by 0.6 MPa to 0.8 MPa. This allows the surface roughness profile parameter Ra value of the treated surface to be controlled between 60 micrometers and 80 micrometers, and the surface cleanliness reaches the Sa 2.5 level of ISO8501-1 standard. In the chemical degreasing and cleaning process, the components of the alkaline degreasing agent aqueous solution by weight percentage are: sodium hydroxide 5-8%, sodium carbonate 10-15%, trisodium phosphate 3-5%, and nonionic surfactant 1-2%, with the remainder being deionized water; the solution temperature is maintained between 70°C and 85°C during the process, and ultrasonic vibration at a frequency of 28 kHz is applied, with the processing time lasting 15 to 20 minutes. In the surface activation and adhesion enhancement treatment step, the phosphating solution is a zinc-based medium-temperature phosphating solution, with the treatment temperature set at 55 to 65 degrees Celsius, the total acidity controlled at 25 to 35 points, the free acidity controlled at 1.0 to 2.0 points, and the soaking time at 10 to 15 minutes.
[0009] Preferably, the application stage of the multilayer composite friction-enhancing coating specifically includes the following sub-steps in sequence: Step of applying epoxy silane coupling agent underlayer: A low-viscosity two-component epoxy silane coupling agent is uniformly sprayed onto the pretreated working surface of the fishtail plate substrate using a high-pressure airless spraying method to form the epoxy silane coupling agent underlayer, the wet film thickness of which is controlled between 8 micrometers and 12 micrometers. The steps for applying a high-strength epoxy resin matrix binder layer are as follows: A modified two-component high-thixotropic epoxy resin binder is uniformly applied to the surface of the epoxy silane coupling agent substrate to form the high-strength epoxy resin matrix binder layer, with a wet film thickness controlled between 250 micrometers and 300 micrometers; and the steps for embedding and fixing hard wear-resistant aggregates are as follows: While the high-strength epoxy resin matrix binder layer is still wet and not gelled, the hard wear-resistant aggregates are immediately and uniformly and densely embedded into the high-strength epoxy resin matrix binder layer using an electrostatic sand-planting system, with the amount of aggregate applied controlled between 1.8 kg and 2.2 kg per square meter.
[0010] Preferably, the epoxy silane coupling agent is γ-glycidoxypropyltrimethoxysilane; The high-strength epoxy resin matrix adhesive layer uses a two-component high-thixotropic epoxy resin adhesive, wherein component A is a bisphenol A type epoxy resin prepolymer with an epoxy equivalent of 184-190 g / eq, and component B is a modified amine curing agent, and nano-silica toughening agent is added to component B. The hard wear-resistant aggregate is fused silicon carbide particles, or metal carbide powders such as tungsten carbide and titanium carbide, or superhard material powders such as artificial single crystal diamond and cubic boron nitride, or special ceramic powders such as silicon nitride and titanium boride, or garnet and fused corundum particles.
[0011] Preferably, the hard wear-resistant aggregate is fused silicon carbide particles with a bimodal particle size distribution, which are composed of a coarse particle portion and a fine particle portion; wherein the coarse particle portion is selected from F60 mesh silicon carbide conforming to FEPA standards, the fine particle portion is selected from F100 mesh silicon carbide conforming to FEPA standards, and the mass mixing ratio of the coarse particle portion to the fine particle portion is 7:3.
[0012] Preferably, the thermal curing process in the thermal curing and post-treatment stage is executed using a preset multi-stage programmed temperature rise curing program, which specifically includes: Pre-curing stage: The workpiece with the aggregate embedded is heated from room temperature to 60 degrees Celsius at a rate of 2 degrees Celsius per minute, and held at this temperature for 40 minutes. Deep curing stage: The temperature is increased from 60 degrees Celsius to 90 degrees Celsius at a rate of 3 degrees Celsius per minute, and then held at this temperature for 120 minutes. Post-curing stage: Increase the temperature from 90 degrees Celsius to 110 degrees Celsius at a rate of 2 degrees Celsius per minute, and hold at this temperature for 60 minutes; After the post-curing stage is completed, the heating system is turned off, and the workpiece is allowed to cool naturally to room temperature in the oven.
[0013] Preferably, the surface activation and adhesion enhancement treatment step is achieved by using laser surface texturing technology to replace chemical phosphating treatment; the laser surface texturing technology specifically involves using a high-power nanosecond pulsed fiber laser and a scanning galvanometer system to precisely etch an array of micron-sized pits or grooves on the working surface to be treated on the fishtail plate substrate, so as to enhance the mechanical bonding force of the subsequent coating through the microstructure constructed by physical methods.
[0014] Beneficial effects This invention provides a friction-enhancing treatment process for fishplates at rail joints. Compared with existing technologies, it has the following advantages: 1. The rail joint fishplate friction enhancement process increases the static friction coefficient of the contact interface from about 0.3 in traditional steel-to-steel contact to more than 0.65 by constructing a composite friction enhancement coating on the fishplate. This results in a significant increase in the longitudinal resistance of the rail joint under the same bolt preload torque. This enhanced locking capability can effectively resist the longitudinal expansion and contraction of the rail caused by huge temperature stress, thereby stabilizing the rail gap width within the minimum range allowed by the design.
[0015] 2. The rail joint fishplate friction enhancement process effectively controls the rail gap width, improving traffic safety and track structure reliability. It can prevent insulation component crushing and track circuit short circuits caused by excessively small or closed rail gaps in summer, as well as severe wheel-rail impact and "low joint" defects caused by excessively large rail gaps in winter. This directly reduces the traffic safety risks caused by joint problems, delays fatigue damage to rails and components in the joint area, and extends their service life.
[0016] 3. The friction-enhancing treatment process for the fishplate of the rail joint increases the joint resistance mainly by increasing the friction coefficient rather than increasing the bolt tightening force. Therefore, it is not necessary to pursue the ultimate bolt tightening torque in on-site construction and daily maintenance. This not only reduces the requirements for construction equipment and personnel skills, but also reduces the difficulty and time cost of operation. It also avoids the risk of fracture caused by bolt overload service and improves the consistency and reliability of joint performance in large-scale applications. Attached Figure Description
[0017] Figure 1 This is a schematic diagram of the processing technology of the present invention. Detailed Implementation
[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0019] Please see Figure 1 The steel rail joint fishplate friction enhancement process provides a technical solution: the process, according to a preset sequence and process parameters, includes a substrate pretreatment stage, a multi-layer composite friction enhancement coating application stage, a thermal curing and post-treatment stage, and a final quality inspection stage. Example 1: The substrate pretreatment stage aims to provide a clean, rough, and high-surface-energy ideal bonding interface for subsequent coating application. It includes the following sequential sub-steps: First, a surface mechanical cleaning treatment is performed. The fishplate substrate to be treated is placed in a dedicated sandblasting device, using angular steel grit or alumina abrasive as the blasting medium. The abrasive particle size is G40. Driven by compressed air at 0.6 MPa to 0.8 MPa, the entire surface of the fishplate substrate, especially the upper and lower jaw areas that will contact the lower part of the rail head and the upper part of the rail bottom, is thoroughly sandblasted. The purpose of this step is to completely remove the oxide scale, rust, original coating, and other attached contaminants from the substrate surface and form a uniform roughened surface. The surface roughness profile parameter Ra value is controlled between 60 micrometers and 80 micrometers, and the surface cleanliness reaches the Sa2.5 level of the international standard ISO 8501-1.
[0020] Next, chemical degreasing and cleaning are performed. The fishtail plate substrate, which has undergone mechanical purification, is completely immersed in an ultrasonic cleaning tank containing an industrial-grade alkaline degreasing agent solution. The alkaline degreasing agent solution consists of, by weight percentage, 5-8% sodium hydroxide, 10-15% sodium carbonate, 3-5% trisodium phosphate, and 1-2% nonionic surfactant, with the remainder being deionized water. The temperature of the solution in the cleaning tank is maintained between 70 and 85 degrees Celsius, and ultrasonic vibration at a frequency of 28 kHz is applied for 15 to 20 minutes. The purpose of this step is to thoroughly remove grease, dust, and other organic contaminants remaining in the micropores on the substrate surface after sandblasting. After the degreasing treatment is completed, the fishtail plate substrate is removed and sequentially rinsed with high-pressure hot water and then rinsed with room temperature deionized water. Finally, it is dried with compressed air in a clean environment to obtain a clean surface free of any oil residue.
[0021] Subsequently, surface activation and adhesion enhancement treatments are performed. The clean and dry fishtail board substrate, with its untreated areas precisely masked using a precision-cut acid-resistant polyimide film, exposes only the upper and lower jaw working surfaces to be coated with the friction-enhancing coating. The fishtail board substrate is then immersed in a phosphating solution, a zinc-based medium-temperature phosphating solution whose main components include phosphoric acid, zinc dihydrogen phosphate, zinc nitrate, and specific accelerators. The temperature of the solution is set at 55°C to 65°C, the total acidity is controlled at 25 to 35 points, and the free acidity is controlled at 1.0 to 2.0 points. The fishtail board substrate is immersed in the phosphating solution for 10 to 15 minutes until a dense, uniform, grayish-white phosphate conversion film forms on its surface. This phosphate film has a microporous structure, which greatly increases the macroscopic and microscopic specific surface area of the substrate, providing an excellent mechanical bonding foundation for the subsequent coating adhesion. After the phosphating treatment, the fishtail board substrate is removed, thoroughly rinsed with deionized water, and completely dried before proceeding to the next stage.
[0022] The multilayer composite friction-enhancing coating application stage is the core technical aspect of this invention. Its goal is to construct a composite coating structure with gradient functional characteristics, consisting of a bottom layer, a matrix layer, and a functional layer, on the pretreated substrate surface. This stage includes the following sequentially executed sub-steps: First, an epoxy silane coupling agent bottom layer is applied. A low-viscosity two-component epoxy silane coupling agent is uniformly sprayed onto the pretreated and masked working surface of the fishtail plate substrate using a high-pressure airless spraying method. One end of the epoxy group of the coupling agent can chemically bond with the subsequent epoxy resin matrix, while the other end of the silane group can form a stable chemical bond with the phosphating film and metal matrix on the substrate surface after hydrolysis. The thickness of the wet film formed by spraying is controlled between 8 micrometers and 12 micrometers. After spraying, it is left to stand at room temperature for 20 to 30 minutes to allow the solvent to fully evaporate and promote the initial reaction between the coupling agent and the substrate.
[0023] Next, a high-strength epoxy resin matrix adhesive layer is applied. A modified two-component high thixotropic epoxy resin adhesive is mixed in a vacuum mixer with component A (epoxy resin prepolymer) and component B (modified amine curing agent) at a mass ratio of 100:42 until a uniform, bubble-free viscous colloid is formed. The epoxy resin is bisphenol A type epoxy resin with an epoxy equivalent of 184-190 g / eq. The modified amine curing agent contains nano-silica toughening agent to improve the impact toughness of the cured coating. Using a precision scraping or robot-controlled automatic spraying system, the mixed epoxy resin matrix adhesive is evenly applied to the surface of the coupling agent-coated underlayer. The thickness of the formed wet film is strictly controlled between 250 and 300 micrometers. The introduction of high thixotropy ensures that the adhesive has good fluidity during application and effectively resists gravity sagging when stationary, ensuring the uniformity of the coating thickness.
[0024] Next, the embedding and fixing steps of the hard wear-resistant aggregate are performed. While the epoxy resin matrix binder layer is still wet and not gelled, the hard wear-resistant aggregate is immediately and uniformly and densely embedded into the binder layer using an electrostatic sand-planting system. The hard wear-resistant aggregate uses electrofused silicon carbide particles with a bimodal particle size distribution. The coarse particles are F60 mesh (average particle size approximately 250 micrometers) silicon carbide conforming to FEPA standards, and the fine particles are F100 mesh (average particle size approximately 150 micrometers) silicon carbide, with a mass mixing ratio of 7:3. This bimodal particle size distribution... The design ensures that coarse particles form the main friction skeleton, while fine particles fill the gaps between the coarse particles, thereby achieving the highest packing density and the largest effective friction contact area. The electrostatic sand planting system charges the silicon carbide particles under the action of a high-voltage electric field and attracts them to the grounded fishtail plate working surface, ensuring that the particles are implanted with their tips perpendicular to the matrix in the optimal orientation and achieving extremely high coverage. The amount of aggregate applied is controlled at 1.8 kg to 2.2 kg per square meter. After sand planting, the entire workpiece is left to stand in a vibration-free environment for 15 minutes to allow the aggregate to settle stably in the binder.
[0025] The thermal curing and post-treatment stage aims to fully cross-link and cure the multi-layer composite coating through a precisely controlled heating process, forming a final structure with stable chemical and physical properties, and removing excess surface deposits. This stage includes the following sub-steps: First, a programmed temperature rise curing process is performed. The fishtail plate workpiece with the aggregate embedded is placed horizontally on a dedicated oven support, and a preset multi-stage temperature rise curing program is started. The first stage is the pre-curing stage, in which the oven temperature is slowly raised from room temperature to 60 degrees Celsius at a rate of 2 degrees Celsius per minute, and held at this temperature for 40 minutes. The purpose of this stage is to allow the epoxy resin matrix to slowly gel, locking the aggregate position and preventing subsequent rapid heating. The first stage is the induction curing stage, which introduces coating defects. The second stage is the deep curing stage, where the temperature is increased from 60 degrees Celsius to 90 degrees Celsius at a rate of 3 degrees Celsius per minute and held at this temperature for 120 minutes. This stage is the main stage for the formation of the epoxy resin network structure. The third stage is the post-curing stage, where the temperature is increased from 90 degrees Celsius to 110 degrees Celsius at a rate of 2 degrees Celsius per minute and held at this temperature for 60 minutes. The purpose of this stage is to make the crosslinking reaction more complete, eliminate internal stress, and maximize the glass transition temperature (Tg) and overall mechanical properties of the coating. After the curing process is completed, the heating system is turned off, and the workpiece is allowed to cool naturally to room temperature in the oven.
[0026] Subsequently, a surface finishing process is performed. After the workpiece has completely cooled, it is removed from the oven, and the polyimide film used for masking is removed. A power brush with medium-hardness nylon abrasive filaments is used to lightly brush the surface of the friction-enhancing coating. The purpose of this step is to remove the outermost loose silicon carbide particles that are only weakly adsorbed by surface tension and are not effectively wrapped by the epoxy matrix, without damaging the firmly embedded aggregate structure. After finishing, the coating surface is thoroughly blown away with clean compressed air at a pressure of 0.5 MPa to ensure that no floating dust particles remain.
[0027] The final quality inspection stage involves quantitative testing of the performance parameters of the finished friction-enhanced fishplate products to ensure they meet design requirements. Inspection items include: measuring the total dry film thickness at multiple predetermined points on the coating surface using an eddy current thickness gauge, with an average value between 350 and 450 micrometers; measuring the arithmetic mean roughness Ra of the coating surface using a contact surface profilometer, with a value between 65 and 85 micrometers; and performing a cross-cut adhesion test according to ASTM D3359, with results meeting a 5B rating, meaning completely smooth cut edges and no peeling between the cuts. Only fishplates that pass all inspections can be marked as qualified and proceed to packaging and storage.
[0028] By executing the complete process described above, this invention ultimately produces a friction-enhancing fishplate. This fishplate has a multi-layered composite friction-enhancing coating on its working surface, characterized by a precise structure and superior performance. From the inside out, this coating consists of a phosphate conversion film layer, an epoxy silane coupling agent underlayer, a high-toughness epoxy resin matrix binder layer, and a hard, wear-resistant aggregate functional layer composed of bimodal silicon carbide particles. This structure ensures extremely high bonding strength between the friction-enhancing coating and the fishplate substrate through chemical bonding and mechanical locking. Simultaneously, the densely arranged and firmly fixed high-hardness silicon carbide particles result in an extremely high macroscopic coefficient of friction on the coating surface. Testing shows that the static friction coefficient between the friction-enhancing fishplate treated with this invention and standard rail steel can stably reach over 0.65, and the dynamic friction coefficient can reach over 0.55. Compared to the untreated steel-to-steel contact surface, its friction performance is improved by over 100%.
[0029] To further verify the significant technical effects brought about by the technical solution of the present invention, the product of Example 1 above was prepared, and a comparative example 1 was also prepared at the same time.
[0030] The main difference between the preparation process of Comparative Example 1 and Example 1 lies in the simplification or omission of several key steps: 1. In the substrate pretreatment stage, the chemical phosphating treatment step is omitted. That is, after alkaline degreasing cleaning and drying, the coating application stage is directly entered.
[0031] 2. In the multi-layer composite friction-enhancing coating application stage, the spraying of the epoxy silane coupling agent underlayer is omitted, and the epoxy resin matrix binder is directly applied to the steel surface that has only undergone sandblasting and degreasing.
[0032] 3. The hard wear-resistant aggregate used is F60 mesh silicon carbide with a single particle size, rather than a mixed aggregate with a bimodal particle size distribution.
[0033] 4. In the heat curing stage, a simplified single-stage curing procedure was adopted: the oven was directly heated to 90 degrees Celsius and kept at a constant temperature for 3 hours, and then cooled naturally.
[0034] The friction-enhanced fishplates prepared in Example 1 and Comparative Example 1, as well as an untreated ordinary P60 fishplate, were used as benchmarks and compared on a specially designed friction performance testing bench. This testing bench can simulate the actual assembly state of rail joints and accurately apply normal pressure and measure tangential force. The quantitative data of the test results are shown in the table below:
[0035] The data comparison in the table above clearly shows that the friction-enhanced fishtail plate (Example 1) prepared by the complete and systematic process disclosed in this invention has performance that far exceeds that of the benchmark ordinary fishtail plate and the simplified Comparative Example 1. Specifically, Example 1 achieved relatively high static and dynamic friction coefficients of 0.68 and 0.57, respectively, which are more than 2.4 times that of ordinary steel-steel contact surfaces and significantly higher than Comparative Example 1. This is directly attributed to the high-density friction surface brought by the bimodal aggregate and the optimized coating structure. Most importantly, the adhesion of Example 1 reached the highest 5B level, demonstrating the extreme effectiveness of the chemical and mechanical composite locking system constructed by the phosphate layer and coupling agent layer. In contrast, Comparative Example 1, which omitted these key steps, showed significant adhesion problems (3B level), which is unacceptable in the long-term vibration and impact environment of railways. In the temperature cycling test simulating long-term service, Example 1 controlled the rail gap change within 1 mm, demonstrating excellent joint locking ability, while ordinary fishplates and Comparative Example 1 showed large rail gap changes, which would lead to a series of track defects in practical applications. Finally, the wear resistance test also proved the robustness and durability of the coating structure of the present invention. Example 2: The material selection for hard wear-resistant aggregates is not limited to silicon carbide. In other examples, other types of hard materials can be selected according to different requirements for cost, hardness, and wear resistance. For example, metal carbide powders such as tungsten carbide and titanium carbide with a Mohs hardness greater than 9 can be selected; or superhard material powders such as artificial single-crystal diamond and cubic boron nitride (CBN) can be selected; or special ceramic powders such as silicon nitride and titanium boride can be selected; or lower-cost mineral-based abrasives such as garnet or fused alumina particles can be selected. These materials can all be used as functional aggregates to achieve the technical effect of improving the coefficient of friction.
[0036] Example 3: The application method of the multilayer composite friction-enhancing coating can be replaced by thermal spraying technology instead of the aforementioned epoxy resin bonding system. Specifically, after completing the substrate pretreatment stage, atmospheric plasma spraying (APS) process is used. The spraying material is a pre-prepared composite powder, which is mechanically mixed with nickel-chromium alloy powder (as the binder phase) and tungsten carbide-cobalt powder (as the wear-resistant phase) in a specific ratio. By adjusting the process parameters such as the power of the plasma spray gun, the powder feeding rate and the spraying distance, a metal-ceramic friction-enhancing coating with a thickness of 200 micrometers to 300 micrometers is directly sprayed onto the working surface of the fishtail plate to form a metallurgical bond between the coating and the substrate, which has higher temperature resistance and impact resistance.
[0037] Example 4: The surface activation and adhesion enhancement treatment steps in the substrate pretreatment stage can be replaced by laser surface texturing technology instead of chemical phosphating. Specifically, a high-power nanosecond pulsed fiber laser is used to precisely etch micron-scale arrayed pits or grooves on the working surface of the fishtail plate through a scanning galvanometer system. The wavelength of the laser is 1064 nanometers and the pulse frequency is 50 kHz. By controlling the scanning speed and power density, microstructures with specific depths, diameters and spacing can be precisely constructed. The microstructures formed by this physical method can also greatly enhance the mechanical bonding force of subsequent coatings, and the process is more environmentally friendly and has higher control precision.
[0038] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0039] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A friction-enhancing treatment process for fishplates of rail joints, applied to the surface modification treatment of fishplate substrates made of metal materials and fiber-reinforced resin matrix composites, characterized in that: The process includes the following steps in a pre-set sequence: Step 1: Substrate pretreatment stage, used to form a clean, rough bonding interface with high surface energy on the working surface to be treated of the fishtail plate substrate. Step 2: Multi-layer composite friction-enhancing coating application stage, used to construct a composite coating structure on the pretreated working surface, consisting of an epoxy silane coupling agent underlayer, a high-strength epoxy resin matrix binder layer, and hard wear-resistant aggregate; Step 3: Thermal curing and post-treatment stage, used to fully cross-link and cure the composite coating structure to form a final friction-enhancing coating area with stable physicochemical properties, and to remove excess surface deposits.
2. The friction-enhancing treatment process for fishplates of rail joints according to claim 1, characterized in that: The substrate pretreatment stage specifically includes the following sub-steps in sequence: Surface mechanical cleaning treatment steps: Sandblasting is used to thoroughly sandblast the entire surface of the fishtail plate substrate, focusing on the upper and lower jaw areas that will contact the rail, in order to remove the oxide scale, rust and other attached contaminants on the surface and form a uniform roughened surface. Chemical degreasing and cleaning process for metal fishtail plates: The fishtail plate substrate, which has undergone mechanical purification, is immersed in an ultrasonic cleaning tank containing an alkaline degreasing agent aqueous solution to remove grease, dust and other organic contaminants remaining in the micropores on its surface. Then, it is sequentially subjected to high-pressure hot water rinsing, deionized water rinsing and compressed air drying. Cleaning steps for fiber-reinforced resin-based composite fishplates: Wipe the surface of the fishplate that is in contact with the rail with acetone or anhydrous ethanol after mechanical cleaning of the fishplate substrate. After cleaning, dry it with compressed air. The surface activation and adhesion enhancement treatment steps for metal fishtail plates are as follows: The clean and dry working surface of the fishtail plate substrate is exposed and immersed in a phosphating solution for treatment until a dense, uniform phosphate conversion film with a microporous structure is formed on its surface to increase the specific surface area of the substrate and provide a mechanical bonding basis for subsequent coatings.
3. The friction-enhancing treatment process for fishplates of rail joints according to claim 2, characterized in that: In the surface mechanical cleaning process, angular steel grit or alumina abrasive is used as the blasting medium. The abrasive has a particle size of G40 and is blasted under compressed air driven by 0.6 MPa to 0.8 MPa. This results in the surface roughness profile parameter Ra value being controlled between 60 micrometers and 80 micrometers, and the surface cleanliness reaching the Sa2.5 level of ISO 8501-1 standard. In the chemical degreasing and cleaning process of the metal fishtail plate, the components of the alkaline degreasing agent aqueous solution by weight percentage are: sodium hydroxide 5-8%, sodium carbonate 10-15%, trisodium phosphate 3-5%, and nonionic surfactant 1-2%, with the remainder being deionized water; the solution temperature is maintained between 70 degrees Celsius and 85 degrees Celsius during the treatment, and ultrasonic vibration at a frequency of 28 kHz is applied, with the treatment time lasting 15 to 20 minutes; In the chemical degreasing and cleaning process of the fiber-reinforced resin matrix composite fishtail plate shown, The concentration of acetone used is 13.5 mol / L; In the surface activation and adhesion enhancement treatment step, the phosphating solution is a zinc-based medium-temperature phosphating solution, with the treatment temperature set at 55 to 65 degrees Celsius, the total acidity controlled at 25 to 35 points, the free acidity controlled at 1.0 to 2.0 points, and the soaking time at 10 to 15 minutes.
4. The friction-enhancing treatment process for fishplates of rail joints according to claim 1, characterized in that: The application stage of the multilayer composite friction-enhancing coating specifically includes the following sub-steps: Step of applying epoxy silane coupling agent underlayer: A low-viscosity two-component epoxy silane coupling agent is uniformly sprayed onto the pretreated working surface of the fishtail plate substrate using a high-pressure airless spraying method to form the epoxy silane coupling agent underlayer, the wet film thickness of which is controlled between 8 micrometers and 12 micrometers. The steps for applying a high-strength epoxy resin matrix binder layer are as follows: A modified two-component high-thixotropic epoxy resin binder is uniformly applied to the surface of the epoxy silane coupling agent substrate to form the high-strength epoxy resin matrix binder layer, with a wet film thickness controlled between 250 micrometers and 300 micrometers; and the steps for embedding and fixing hard wear-resistant aggregates are as follows: While the high-strength epoxy resin matrix binder layer is still wet and not gelled, the hard wear-resistant aggregates are immediately and uniformly and densely embedded into the high-strength epoxy resin matrix binder layer using an electrostatic sand-planting system, with the amount of aggregate applied controlled between 1.8 kg and 2.2 kg per square meter.
5. The friction-enhancing treatment process for fishplates of rail joints according to claim 1, characterized in that: The epoxy silane coupling agent is γ-glycidoxypropyltrimethoxysilane; The high-strength epoxy resin matrix adhesive layer uses a two-component high-thixotropic epoxy resin adhesive, wherein component A is a bisphenol A type epoxy resin prepolymer with an epoxy equivalent of 184-190 g / eq, and component B is a modified amine curing agent, and nano-silica toughening agent is added to component B. The hard wear-resistant aggregate is silicon carbide particles, or fused silicon carbide particles, or tungsten carbide, or titanium carbide metal carbide powder, or artificial single crystal diamond, cubic boron nitride superhard material powder, or silicon nitride, titanium boride special ceramic powder, or garnet, or fused corundum particles.
6. The friction-enhancing treatment process for fishplates of rail joints according to claim 1, characterized in that: The hard wear-resistant aggregate uses fused silicon carbide particles with a bimodal particle size distribution, which are composed of a coarse particle portion and a fine particle portion. The coarse particle portion is selected from F60 mesh silicon carbide conforming to FEPA standards, and the fine particle portion is selected from F100 mesh silicon carbide conforming to FEPA standards. The mass mixing ratio of the coarse particle portion to the fine particle portion is 7:
3.
7. The friction-enhancing treatment process for fishplates of rail joints according to claim 1, characterized in that: The thermal curing process in the aforementioned thermal curing and post-treatment stage is executed using a preset multi-stage programmed temperature rise curing program, which specifically includes: Pre-curing stage: The workpiece with the aggregate embedded is heated from room temperature to 60 degrees Celsius at a rate of 2 degrees Celsius per minute, and held at this temperature for 40 minutes. Deep curing stage: The temperature is increased from 60 degrees Celsius to 90 degrees Celsius at a rate of 3 degrees Celsius per minute, and then held at this temperature for 120 minutes. Post-curing stage: Increase the temperature from 90 degrees Celsius to 110 degrees Celsius at a rate of 2 degrees Celsius per minute, and hold at this temperature for 60 minutes; After the post-curing stage is completed, the heating system is turned off, and the workpiece is allowed to cool naturally to room temperature in the oven.
8. The friction-enhancing treatment process for fishplates of rail joints according to claim 1, characterized in that: The substrate pretreatment stage also includes a surface activation and adhesion enhancement treatment step for the fiber-reinforced resin-based composite fishtail plate, which is achieved by using laser surface texturing technology to replace chemical phosphating treatment. Specifically, the laser surface texturing technology involves using a high-power nanosecond pulsed fiber laser and a scanning galvanometer system to precisely etch an array of micron-sized pits or grooves on the working surface to be treated on the fishtail plate substrate. This microstructure, constructed through physical methods, enhances the mechanical bonding force of subsequent coatings.
Citation Information
Patent Citations
Improved damping fish plate
CN201024360Y